From Biological Resources to Market Value: A Mediation Analysis of Disclosure Practices and Firm Characteristics - Nasution, Yan Noviar; Kohar, Abdul (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to examine the effect of biological asset intensity and firm size on the disclosure of biological assets and their direct and indirect impacts on firm value in the agricultural sector. The research objects are agricultural companies listed on the Indonesia Stock Exchange (IDX) during the 2016–2021 period. Out of a population of 25 companies, 12 were selected as the sample using an explanatory survey approach with purposive sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that biological asset intensity and firm size have a positive effect on the disclosure of biological assets. Furthermore, biological asset disclosure positively influences firm value. The findings also reveal that the effect of biological asset intensity and firm size on firm value is significantly mediated by the disclosure of biological assets. These results highlight the importance of transparent reporting of biological assets in enhancing firm value and reinforce the relevance of agency theory in addressing information asymmetry in the agricultural sector. Keywords: Biological Asset Intensity, Firm Size, Disclosure of Biological Assets, Firm Value